Challenging Cases in Neurology: Neurologic Complications of COVID-19 - Horta, Lucas; Bakhtyari, Ava; Greige, Tatiana; Anand, Pria (Seminars in Neurology, 2022)
Since the first reported cases of pneumonia in December 2019, coronavirus disease 2019 (COVID-19) has rapidly become recognized as a multisystem illness, with known effects on virtually every organ system. In particular, neurologic complications of COVID-19 have been reported since the beginning of the pandemic in both ambulatory patients with mild disease and critically ill patients. Although it remains unclear whether severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has the potential to directly invade the central nervous system, strokes and other neurovascular complications, sequelae of critical illness and metabolic derangements, parainfectious inflammatory disorders, and a poorly understood post-COVID syndrome have all been reported in patients with COVID-19. Here, we describe cases representing a diverse range of neurologic complications in patients infected with COVID-19.
Keywords: COVID-19; encephalitis; GAD-65 encephalitis; osmotic demyelination syndrome; anterior biopercular syndrome